P2X7 Receptors as a Transducer in the Co-Occurrence of Neurological/Psychiatric and Cardiovascular Disorders: A Hypothesis. (10th August 2009) - Skaper, Stephen D.; Giusti, Pietro
Abstract : Background. Over-stimulation of the purinergicP 2 X 7 receptor may bring about cellular dysfunction and injury in settings of neurodegeneration, chronic inflammation, as well as in psychiatric and cardiovascular diseases. Here we speculate howP 2 X 7 receptor over-activation may lead to the co-occurrence of neurological and psychiatric disorders with cardiovascular disorders. Presentation. We hypothesize that proinflammatory cytokines, in particular interleukin-1β, are key players in the pathophysiology of neurological, psychiatric, and cardiovascular diseases. Critically, this premise is based on a role for theP 2 X 7 receptor in triggering a rise in these cytokines. Given the broad distribution ofP 2 X 7 receptors in nervous, immune, and vascular tissue cells, this receptor is proposed as central in linking the nervous, immune, and cardiovascular systems. Testing. Investigate, retrospectively, whether a bidirectional link can be established between illnesses with a proinflammatory component (e.g., inflammatory and chronic neuropathic pain) and cardiovascular disease, for example, hypertension, and whether patients treated with anti-inflammatory drugs have a lower incidence of disease complications. Positive outcome would indicate a prospective study to evaluate therapeutic efficacy ofP 2 X 7 receptor antagonists. Implications. It should be stressed that sufficient direct evidence does not exist at present supporting our hypothesis. However, a positive outcome would encourage the further development ofP 2 X 7 receptor antagonists and their application to limit the co-occurrence of neurological, psychiatric, and cardiovascular disorders.